Investigation of enhancing multi-gas transport ability of coalbed methane reservoir by oxidation treatment. (15th October 2020) - Chen, Mingjun; Lu, Yu; Kang, Yili; You, Lijun; Chen, Zhangxin; Liu, Jiang; Li, Peisong
Highlights: Oxidation reaction between different oxidants and coals of different ranks are compared. Desorption acceleration of coals after oxidation treatment is determined. A workflow of evaluating multi-gas transport ability of coals after oxidation is provided. Abstract: Subbituminous coal (Coal S) and anthracite coal (Coal A) were taken as the coal samples and H2 O2, NaClO and ClO2 as the oxidants to investigate multi-gas transport ability enhancement of coalbed methane reservoir after oxidation. Thin section, dissolution rate and organic carbon content were measured to analyze the mechanism for different coal ranks and various oxidants. The dissolution rate of Coal A was greater than Coal S because large amounts of ferrous ions in Coal A had strong catalytic effect on Fenton reaction. However, there was large amounts of siderite composed of ferric ions in Coal S, which did not catalyze Fenton reaction. Meanwhile, the adsorption/ desorption behavior of both raw and treated coal samples was measured. Results show that, besides reaction between oxidants and organic matter/ pyrite/ clay minerals could destroy methane adsorption point in coals, weakening methane adsorption capacity. Also, the gas transport channels were widened and interconnected due to the oxidation dissolution and significant temperature increment during oxidation reaction. It is indicated that the reaction between coals and oxidants accelerated methane desorption, widened the methane mass transfer channel, and finally enhanced the methane multi-gas transport ability of methane in coal. The order of multi-gas transport ability enhancement by oxidation treatment under the condition of similar redox potential of oxidants was Coal ASFW  > Coal AClO2  > Coal ANaClO  > Coal AH2O2 and that of Coal S was Coal SSFW  > Coal SH2O2  > Coal SNaClO  > Coal SClO2 .